PERTANGGUNGJAWABAN PIDANA TENAGA MEDIS YANG MELAKUKAN KESALAHAN DIAGNOSA TERHADAP PASIEN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2014 TENTANG TENAGA KESEHATAN - Johana Supra Silaban; Zulfikar Jaya Kusuma; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
From a legal standpoint, negligence or error will be related to the nature of illegal acts carried out by people who are capable of being responsible. A person is said to be able to be responsible if he can realize the true meaning of his actions. And an act is categorized as